Pengaruh Faktor Individu, Organisasi dan Perilaku terhadap Kepatuhan Perawat dalam Melaksanakan Hand Hygiene di Ruang Rawat Inap Rumah Sakit Tk. II D - Fauzi, Neila; Azzuhri, Misbahuddin; Ahsan (Universitas Brawijaya, Indonesia, 2015)
This study aims to determine the effect of individual, organization, and behaviortowards nurses'hand hygiene compliance. The design of this study uses analytic descriptivestudy design with cross sectional approach on 71 respondents. The data analysis uses descriptivestatistical test, multiple linear regression analysis, hypothesis testing, anddominant variabletests. Individuals, organizations and behaviors significantly influence nurses'hand hygienecompliance. Individual variable dominant has an influence on nurses' hand hygiene compliance